COMPARISON OF PULSATILITY INDEX (PI) AND RESISTIVE INDEX (RI) BETWEEN FETAL LEFT AND RIGHT MIDDLE CEREBRAL ARTERIES: Life Science -Medical Psychology - NALAINI, FARHAD; GHARIB SALEHI, MOHAMMAD; FARSHCHIAN, NAZANIN (International Journal of Life Science and Pharma Research, 2018)
As the origins of the common carotid arteries and consequently middle cerebral arteries (MCAs) are different on the left and right side, we hypothesized that whether there is any difference in the pulsatility index (PI) and resistive index (RI) of left and right MCAs of fetuses suspected to have intrauterine growth restriction (IUGR). To compare the PI and RI between fetal proximal sites of the right and left MCAs. A total of 50 pregnant women with mean (±SD) age of 27 (±6.12) years, mean (±SD) gestational age of 35.1 (±2.8) weeks were included. RI and PI of both left and right MCAs (proximal location) were measured. The correct technique for MCA peak systolic volume (PSV) was done with long axis of the fetal head parallel to the scanner probe with in sonation angle as close as possible to 0°. Mean (±SD) PI in the right and left MCAs were respectively 1.67 (±0.33) and 1.63 (±0.32), P= 0.2. Mean (±SD) RI in the right and left MCAs were respectively 0.79 (±0.06) and 0.78 (±0.07), P= 0.68. No significant difference existed regarding the PI and RI values between right and left MCAs. Either left or right MCA can be imaged during color Doppler ultrasound examination of fetuses suspected to have IUGR.